THE NARRATIVE STRUCTURE AND THE FUNCTIONS OF THE NARRATOR IN MANUEL GONZALEZ PRADA’S ANECDOTES - Granda Rangel, Mario (2022)
The purpose of this article is to review the general characteristics of the anecdote and study the use that Manuel González Prada (1848-1918) makes of it from the narratological categories of narrative structure and the functions of the narrator. From this perspective, we propose that the anecdotes of the Peruvian writer not only served him to spread the anarchist ideology in the city of Lima, but also to propose a realistic representation of the society of his time. For this end, we will analyze and comment five anecdotes published in the anarchist weekly newspapers “El libre pensamiento” and “Los parias”.